Leg Length and Weight: Implication on Exercise Intensity - Airah Bliss M Eleccion (Randwick International of Education and Linguistics Science Journal, 2024)
Practical assessment in Physical Education is one of the most crucial ways of measuring student’s physical ability. This study examined the influence of leg length and body weight on exercise intensity during a 3-minute step test, addressing a gap in fitness assessment practices that often overlook individual physical differences. The purpose of this study was to determine the influence of leg length and body weight on exercise intensity to promote safety measures in practical assessment of Physical Education. Employing a descriptive correlational design, the research analyzed data from 167 college students in Gingoog City, Philippines, using descriptive statistics, frequency distribution, and regression analysis. The findings revealed leg length and body weight have significant influence on the outcome variables. The study concludes that both leg length and body weight significantly influenced exercise intensity, necessitating a re-evaluation of fitness testing methods to account for these individual differences. This result suggests that physical educators, sports coaches, and fitness instructors may consider leg length and weight in fitness assessments and training programs, advocating for personalized approaches to ensure equitable and safe physical fitness evaluation practices.